92 Non-inferiority prospective randomized controlled trial on simple hysterectomy versus radical hysterectomy in early stage cervical cancer. An interim analyzis of lesser trial. (18th September 2019) - Carneiro, V; Paulo Batista, T; Rodrigues de Andrade Neto, M; Vieira Barros, A; Licio Rocha Bezerra, A; de Olanda Lima Dornelas Camara, L; Moreira Ramalho, N; Angelica Lucena, M; Fontão, D; Tancredi, R; César Silva Júnior, T; Baiocchi, G
Abstract : Objectives: To analyze if simple hysterectomy does not have less efficacy and safety compared to radical hysterectomy in treatment of early stage cervical cancer. Methods: An open label non-inferiority prospective randomized controlled trial included 40 patients with stages IA2 to IB1 (≤2cm) cervical cancer. The patients were randomized 1:1 in simple hysterectomy or modified radical hysterectomy and pelvic lymphadenectomy between May 2015 and April 2018. Health-related quality of life was assessed (EORTC QLQ-C30). Primary endpoint was disease free survival in 3 years and secondary endpoints was overall survival, morbidity, and quality of life. Results: Clinical and pathological characteristics were well balanced between treatment groups. Thirty-two (80%) patients were squamous cell carcinomas and 3 (7.5%) cases had metastatic lymph node. The median surgical time was greater for the radical hysterectomy group (150 vs. 199.5 minutes;p=0.003). Postoperative bladder catheterization days were also higher after radical hysterectomy (p=0.043). There was no postoperative mortality and postoperative complication rate was not statistically different (15% and 20%;p=1, 0). Global health, quality of life and physical functioning scores were not different between groups until 6 months of follow-up. There was no difference in adjuvant treatment between groups (30% and 20%;p=0.48). The median follow-up time was 16.2 months and the 2-year disease free survival was 95% and 100% for the simple hysterectomy and modified radical groups, respectively (p=0.405). There was only 1 death due to cancer in the simple hysterectomy arm. Conclusions: This interim analysis suggests low morbidity and safety for simple hysterectomy for early stage cervical cancer compared to radical hysterectomy.